Associations of COVID-19 lockdown with birth weight in China - Chen, Yumeng; Fan, Jingjie; Li, Xiaowei; Ye, Yufeng; Lv, Yanyun; Zheng, Suijin; Hu, Jianxiong; Pu, Yudong; Liu, Tao (Frontiers in Pediatrics, 2024)
During the special period of the global spread of COVID-19, pregnant women are sensitive groups to the impacts of COVID-19 epidemic. However, the effects of lockdown measures implemented in response to the COVID-19 on fetal birthweight remain unclear.This study investigated the associations of COVID-19 lockdown with birth weight in Chinese population.We collected 730,153 data of participants from hospitals of five cities in the south of China, we defined the time period of level I response (1/23 --2/24/2020) as level I lockdown, and women who were pregnant during level I lockdown as the exposure group. Women who were pregnant during the same calendar month from 2015 to 2019 were defined as the unexposed group. We quantitatively estimate the individual cumulative exposure dose by giving different weights to days with different emergency response levels. Generalized linear regression models were used to estimate the association between COVID-19 lockdown exposure with birth weight and risk of low birth weight (<2500g) and macrosomia (>4000g).The birth weight of the exposed group is heavier than the unexposed group (3238.52 vs 3224.11 g: adjusted β=24.39 g [95%CI, 21.88, 26.91 g]). The exposed group had a higher risk of macrosomia (2.8% vs 2.6%; adjusted OR=1.17 [95%CI, 1.12, 1.22]). More obvious associations were found between COVID-19 lockdown and macrosomia in women who experienced the lockdown in their early pregnancy. Women who experienced the lockdown at their 4-7 weeks of pregnancy showed statistically significant heavier birth weight than unexposed group (after adjustment): β=1.28 (95%CI: 1.11, 1.46) g. We also observed a positive association between cumulative exposure dose of COVID-19 lockdown in all pregnant women and birth weight, after divided into four groups, Q1: